Processes and Microorganisms Involved in the Marine Nitrogen Cycle: Knowledge and Gaps - Pajares, Silvia; Ramos, Ramiro (Frontiers in Marine Science, 2019)
Nitrogen (N) is a key element for life in the oceans. It controls primary productivity in many parts of the global ocean, consequently playing a crucial role in the uptake of atmospheric carbon dioxide. The marine N cycle is driven by multiple biogeochemical transformations mediated by microorganisms, including processes contributing to the marine fixed N pool (N2 fixation) and retained N pool (nitrification, assimilation, and dissimilatory nitrate reduction to ammonia), as well as processes contributing to the fixed N loss (denitrification, anaerobic ammonium oxidation and nitrite-dependent anaerobic methane oxidation). The N cycle maintains the functioning of marine ecosystems and will be a crucial component in how the ocean responds to global environmental change. In this review, we summarize the current understanding of the marine microbial N cycle, the functional N genes involved, the ecology and distribution of the participating microorganisms, and the main impacts of anthropogenic activities on the marine N cycle.